Translation Analysis in Sentence Patterns Found in the “Good Earth” (e-Journal of Linguistics, 2023)
This study aims to: (i) analyze the tree diagram structure of sentencepatterns found in the novel “The Good Earth”, (ii) analyze the types oftranslation shifts in sentence patterns in the translation process thatwere found in the data source. The novel entitled “The Good Earth” is afamous literary work that was written by Pearl S. Buck. It told aboutfamily life in a village in China before the world war I. This novel wasthe best seller at that time. This research focuses on The SyntaxAnalysis and Its Translation Found on Sentence Patterns in the storyfrom novel entitled “The Good earth”. This study also focuses onanalyzing the tree diagram structure and the types of translation shifts intranslating from the source language into target language. The analysisapplied the theory of sentence patterns that was proposed by Quirk andGreenbaum and the theory of translations shift proposed by Catford.The process of collecting data was started by reading the novel in orderto understand the novel entitled “The Good Earth” and observe the dataof sentence patterns that could be taken from the data source. In themethod of collecting data, the novel was read in order to find out dataof complex sentences and simple sentence that were found in the novel.